Comunicação mercadológica e entretenimento nas redes digitais: a convocação do consumidor conectado - Duarte, Gracy Cristina Astolpho (2016)
This study presents the research that investigated the strategies used in advertising productions based on entertainment dynamics that focus on customers connected through social networks. Empirical research aimed at understanding the relationship between communication, consumption, entertainment and social networks in advertising campaigns from recognized brands in Brazil. By using the netnographic method and considering the last four years for the corpus, the research selected five advertising campaigns with major social networks repercussion. The methodology for the treatment of the selected material combined content analysis and a critical-descriptive evaluation of the various elements in the selected campaigns. In today s consumer society, advertising and digital media are important resources for production markets of material and symbolic goods. According to the analysis proposed in this study, social network websites are considered as facilitators of a dialogue between brands and costumers. Their intelligent monitoring systems become important marketing resources once they provide valuable information and metrics about the profiles and preferences of customers. Therefore, modern advertising adapts its traditional resources of creative narrative and persuasive discourse into productions that make use of entertainment to present playful proposals that draw the attention of online customers, engaging them in interactions mediated by the brand as part of everyday leisure activities. As can be seen in this investigation, engaging the online consumer and leading him or her to an interaction with those brands, has become a strategic move in contemporary advertising. From the point of view of the market, the consumer is taken as the active subject of social relations that become especially attractive in quantified digital social networks. Thus, what we have here as the convocation of the online connected customer.